What are Infertility Treatment Center Websites Telling Couples about Male Factor Infertility?. Issue 6 (November 2016) - Leung, Andrew K.; Khan, Zehra; Patil, Dattatraya; Mehta, Akanksha
Abstract : Introduction: : We evaluated patient directed information provided on the websites of infertility treatment centers. Methods: : We identified 428 infertility treatment centers based on the 2011 CDC (Centers for Disease Control and Prevention) Fertility Clinic Success Rates Report. The website of each center was evaluated for the presence and/or description of terms related to the etiology, workup and treatment of male factor infertility using a standardized data abstraction form. Differences in the variables were examined with respect to United States Census Bureau geographic regions, academic center status and affiliation with urologists. The Flesch‐Kincaid readability score was assessed. Results: : Only 78% of websites acknowledged a male factor etiology for infertility, 85% mentioned any evaluation of the male partner, 63% mentioned any treatment options for male factor infertility and 23% discussed referral to a urologist. When stratified by geographic region, academic status and urologist affiliation, differences in the variables of interest were most likely when stratified by urologist affiliation. The median website reading level was twelfth grade. Conclusions: : Patient directed information pertaining to the etiology, workup and treatment of male factor infertility on the websites of infertility treatment centers is variable at best. Etiology is completely lacking on more than 20% of websites. It is likely that couples relying on Internet based information regarding infertility evaluation and treatment are not well informed about the importance or the benefit of a male factor evaluation.